Faktor-Faktor Yang Berhubungan Dengan Perilaku Ibu Rumah Tangga Dalam Pengelolaan Sampah Rumah Tangga Di Gampong Anoi Itam Kecamatan Sukajaya Sabang Tahun 2022 - Salsabilla Suci; Zulkifli Ak; Ramadhaniah Ramadhaniah (Journal of Health and Medical Science, 2023)
Community behavior in managing waste is one of the environmental health behaviors. The emergence of the waste problem cannot be separated from the behavior of the community as waste producers and managers, therefore community behavior is the most important variable in waste management and its success must be supported by a high level of public awareness. This research is descriptive analytical with cross sectional design. The population in this study were housewives in Anoi Itam Village, Sukajaya Sabang District, totaling 71 respondents. Sampling was done by proportional random sampling technique. Data analysis used univariate and bivariate analysis, with chi square statistical test. Data collection was carried out on 27 February to 1 March 2022. The results showed that mothers with poor waste management behavior (50,7%), housewives aged 28-39 years (49,3%), housewives with low education (45,1%), mothers with low income low family (74.6%), mothers with good knowledge (83.1%), mothers with positive attitudes (83.1%), no infrastructure (59.7%). Bivariate analysis showed that there was a relationship between knowledge and waste management behavior (p = 0.000), meaning that the better the mother's knowledge, the better the behavior towards waste management, and there was no relationship between age, education, family income, knowledge, attitudes, and infrastructure.